1998
DOI: 10.1146/annurev.physchem.49.1.173
|View full text |Cite
|
Sign up to set email alerts
|

FAST EVENTS IN PROTEIN FOLDING: The Time Evolution of Primary Processes

Abstract: Most experimental studies on the dynamics of protein folding have been confined to timescales of 1 ms and longer. Yet it is obvious that many phenomena that are obligatory elements of the folding process occur on much faster timescales. For example, it is also now clear that the formation of secondary and tertiary structures can occur on nanosecond and microsecond times, respectively. Although fast events are essential to, and sometimes dominate, the overall folding process, with a few exceptions their experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
170
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(174 citation statements)
references
References 127 publications
2
170
0
1
Order By: Relevance
“…The T-jump before transient DVE probing is created by nanosecond excitation of the OD stretch overtone of the D 2 O buffer solution at ϭ 2 m. Picosecond vibrational relaxation raises the temperature of the solution on the time scale of the excitation pulse (15). The 6-mJ, 8-ns T-jump pulse is obtained from a beta barium borate (BBO)-based optical parametric oscillator pumped by the output of a 20-Hz, frequency-doubled, Q-switched Nd:yttrium͞aluminum-garnet laser and focused to a 500-m diameter at the sample.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The T-jump before transient DVE probing is created by nanosecond excitation of the OD stretch overtone of the D 2 O buffer solution at ϭ 2 m. Picosecond vibrational relaxation raises the temperature of the solution on the time scale of the excitation pulse (15). The 6-mJ, 8-ns T-jump pulse is obtained from a beta barium borate (BBO)-based optical parametric oscillator pumped by the output of a 20-Hz, frequency-doubled, Q-switched Nd:yttrium͞aluminum-garnet laser and focused to a 500-m diameter at the sample.…”
Section: Methodsmentioning
confidence: 99%
“…Optical and IR spectroscopies such as fluorescence-based methods (10,11), time-resolved circular dichroism (12), Raman (13), and IR absorption (14,15) are desirable in fast folding experiments because they have the intrinsic time resolution to follow the fastest processes. Nevertheless, relating these experiments to nuclear coordinates that characterize a protein structure or conformation is not trivial, particularly in the presence of disorder.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge about folding transitions can aid in the understanding of biological activity, as biological activity is often regulated by the higher order structure [1]. However, the lifetimes of many partially folded species are usually on the order of hundreds of microseconds to fractions of a second, thus making it difficult to study these intermediates using X-ray or NMR methods [2]. With the development of electrospray ionization (ESI), many mass spectrometry-based methodologies have been established to elucidate the higher order structure of biomolecules.…”
Section: Introductionmentioning
confidence: 99%
“…Temperature jump and other rapid perturbation methods have shown that isolated helices and ␤-hairpins form and decay over a time window ranging from Ϸ100 ns to several microseconds (4,5). Recent advances in rapid mixing techniques combined with structurally informative spectroscopic probes made it possible to resolve conformational events on the submillisecond time scale preceding the rate-limiting step in the folding of globular proteins (6)(7)(8)(9).…”
mentioning
confidence: 99%